GIMÉNEZ LÓPEZ, Enrique. El lado oscuro de las luces en las tierras alicantinas del siglo XVIII. Alicante: Instituto Alicantino de Cultura Juan Gil-Albert, 2017. - Miguel RODRÍGUEZ CANCHO (Cuadernos Dieciochistas)
Reseña bibliográfica.